Governance, order, and the International Criminal Court between real politik and a cosmopolitan court - Roach, Steven C. (Oxford : Oxford University Press, 2009)
How has the International Criminal Court been able to evolve into a fairly effective, albeit relatively untested multi-level model of global governance? This volume explores this question and the novel predicament it represents for understanding the challenges of extending global governance and promoting global justice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International Criminal Court; International criminal courts; International relations; International cooperation; International organization